Whose future?: Epistemic challenges to the collective ‘we’ in long-term governance - Martin Böhnert (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis, 2025)
Building on insights from Science & Technology Studies and epistemology, this article critically examines the epistemic underpinnings of long-term governance (LTG), particularly its implicit assumptions about temporality, collective agency, and the perception of issues that shape governance practices. I identify three key challenges: (i) the tendency to conceive of futures as discrete endpoints rather than relational processes, (ii) the epistemic and political implications of an anticipatory ‘we’ that privileges dominant narratives while marginalizing others, and (iii) the largely unconsidered epistemic structures that implicitly determine what is perceived as imaginable futures. Addressing these challenges, I conclude by considering whether alternative conceptual frameworks that foreground contextuality and plurality might offer a more differentiated approach to LTG.